2004
DOI: 10.1111/j.1469-8137.2004.01254.x
|View full text |Cite
|
Sign up to set email alerts
|

Xylem transport and shoot accumulation of lumichrome, a newly recognized rhizobial signal, alters root respiration, stomatal conductance, leaf transpiration and photosynthetic rates in legumes and cereals

Abstract: Summary• Root respiration, stomatal conductance, leaf transpiration and photosynthetic rates were measured in phytotron and field-grown plants following the application of 5 or 10 n M lumichrome, 10 n M ABA (abscisic acid) and 10 ml of 0.2 OD600 infective rhizobial cells.• Providing soybean and cowpea roots with their respective homologous rhizobia and/or purified lumichrome increased the concentration of this molecule in xylem sap and leaf extracts. Relative to control, rhizobial inoculation and lumichrome ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 23 publications
1
36
0
Order By: Relevance
“…Mechanistically, this can happen through the action of rhizobial products such as abscisic acid (Phillips and Torey, 1970) or lumichrome (Phillips et al, 1999) in decreasing leaf stomatal conductance and reducing water loss via transpiration. A recent study has, in fact, shown that the application to roots of 10 nM lumichrome, 10 nM abscisic acid, or 10 mL of cultured infective cells of B. japonicum strain WB74 resulted in significantly decreased leaf stomatal conductance and reduced water loss via transpiration in soybean leaves (Matiru and Dakora, 2005). Taken together, our data suggest that bacterial presence in the rhizosphere can trigger plant response to drought, especially in arid environments where water can be a limiting factor for plant growth.…”
Section: Discussionmentioning
confidence: 59%
“…Mechanistically, this can happen through the action of rhizobial products such as abscisic acid (Phillips and Torey, 1970) or lumichrome (Phillips et al, 1999) in decreasing leaf stomatal conductance and reducing water loss via transpiration. A recent study has, in fact, shown that the application to roots of 10 nM lumichrome, 10 nM abscisic acid, or 10 mL of cultured infective cells of B. japonicum strain WB74 resulted in significantly decreased leaf stomatal conductance and reduced water loss via transpiration in soybean leaves (Matiru and Dakora, 2005). Taken together, our data suggest that bacterial presence in the rhizosphere can trigger plant response to drought, especially in arid environments where water can be a limiting factor for plant growth.…”
Section: Discussionmentioning
confidence: 59%
“…NGR234 (Theunis et al 2004 ); pentacyclic triterpenoid lipids, hopanoids, in bradyrhizobia and Rhizobium sp. (Kannenberg et al 1995 ); a quorum sensor-AHL and a non-AHL quorum sensor, bradyoxetin, in bradyrhizobia (Loh et al 2002 ;Mathesius et al 2003 ); and a plant growth enhancer, lumichrome, in S. meliloti Matiru and Dakora 2005 ). These compounds are required at different stages of the symbiotic development from root colonization to the formation of a functioning nodule (Cooper 2007 ).…”
Section: Rhizobial Secretome Also Contains Several Other Important Comentioning
confidence: 98%
“…Besides photochemical action, production of lumichrome from riboflavin by cleavage of the ribityl group can occur also by enzymatic mechanism. It is reported that several microorganisms present in the rhizosphere produce lumichrome that act as signal molecule for stimulating plant growth (Matiru & Dakora, 2005;Phillips et al, 1999). These results suggest that lumichrome is not just a waste metabolite, but can play an important role in the biological cycles.…”
Section: Introductionmentioning
confidence: 96%